Yarn level simulation of warp-knitted clothing elements – first results and challenges - Haisang Liu; Yordan Kyosev; Gaoming Jiang (Communications in Development and Assembling of Textile Products, 2022)
To simulate a warp-knitted product with a specific shape, a mesh-based model for modeling and simulation is proposed. The three-dimensional geometry of the final fabric is represented as a set of polygons, each of them containing information about the 3D orientation of the yarns in the warp knitted structure. Using spatial mapping, stitch coordinates are transformed from the flat mesh model to the three-dimensional mesh model and the final rendering is accomplished. The method provides yarn level data for the complete structure and can be used for speeding up the design process of clothing with warp-knitted products. Several challenges with the larger data amount and possible ways for their solutions are discussed.